2013
DOI: 10.1103/physrevlett.111.245003
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Electron Beams from Beam-Driven Plasma Accelerators by Wakefield-Induced Ionization Injection

Abstract: We propose a new and simple strategy for controlled ionization-induced trapping of electrons in a beam-driven plasma accelerator. The presented method directly exploits electric wakefields to ionize electrons from a dopant gas and capture them into a well-defined volume of the accelerating and focusing wake phase, leading to high-quality witness bunches. This injection principle is explained by example of three-dimensional particle-in-cell calculations using the code OSIRIS. In these simulations a high-current… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 40 publications
0
66
0
Order By: Relevance
“…Besides the demands for high beam energies, these applications entail stringent requirements with regard to the beam quality. While a number of numerical studies [6][7][8][9][10][11] indicated the potential of PWFAs to generate high quality beams, one of the major challenges constitutes the preservation of these qualities during the witness beam extraction and transport to the interaction region. In addition, the beams may have to be transported in between successive plasma sections and re-injected without significant quality deterioration in staged acceleration concepts, such as proposed e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the demands for high beam energies, these applications entail stringent requirements with regard to the beam quality. While a number of numerical studies [6][7][8][9][10][11] indicated the potential of PWFAs to generate high quality beams, one of the major challenges constitutes the preservation of these qualities during the witness beam extraction and transport to the interaction region. In addition, the beams may have to be transported in between successive plasma sections and re-injected without significant quality deterioration in staged acceleration concepts, such as proposed e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These applications are in particular relevant to PWFA, where low ionization thresholds and multiple gas types can be used. Here the gas density of different gas species can be uniform over the whole acceleration stage-whereas the production of multicomponent mixtures with (independently) differing, localized gas density profiles [29,38] is experimentally challenging.…”
Section: Fig 2 On-axis Density Lineouts For Cases (I) and (Ii)mentioning
confidence: 99%
“…2(b), the situation is substantially different due to the fact, that preionized hydrogen is used. Therefore the wakefield is much stronger and would at the same hydrogen density ionize and even trap helium electrons [24,29,35], which is unwanted here. Because of that, the hydrogen/helium densities are chosen an order of magnitude lower, increasing λ p;H ≈ 334 μm, and the driver beam charge Q was reduced from 3 to 1 nC.…”
Section: Fig 2 On-axis Density Lineouts For Cases (I) and (Ii)mentioning
confidence: 99%
See 2 more Smart Citations